Present‐Day Subsidence in the Ganges‐Brahmaputra‐Meghna Delta: Eastern Amplification of the Holocene Sediment Loading Contribution. Issue 19 (10th October 2019) - Krien, Y.; Karpytchev, M.; Ballu, V.; Becker, M.; Grall, C.; Goodbred, S.; Calmant, S.; Shum, C. K.; Khan, Z.
Abstract: The subsidence of the Ganges‐Brahmaputra‐Meghna Delta (GBMD) drastically increases the adverse impacts of coastal flooding and exacerbates the vulnerability of populations from ongoing rapid sea level rise. We focus here on estimating the present‐day subsidence rates induced by the loading of sediments continuously deposited within the GBMD over the past 11, 000 years. By constructing a realistic GBMD 3‐D numerical model with laterally variable mantle and lithospheric structure, we demonstrate for the first time that the presence of the strong Indian Craton and the weakened Indo‐Burma margin results in significant amplification of subsidence driven by sediment loading in the eastern part of the delta, where the population density is the highest (>1, 000 habitants per km 2 ). Although uncertainties remain regarding the amplitude of subsidence, the rate estimates (2–3 mm/year) are found to be comparable to the present‐day global mean sea level rise. Plain Language Summary: Using 3‐D numerical models, we show that the deformation of the Earth surface due to the weight of sediments deposited in the Ganges‐Brahmaputra‐Meghna Delta (GBMD) is probably larger than previously found and induce significant land vertical downward motions in the eastern part of the delta. This process is intimately linked to the complex geological setting of the GBMD (Indian Craton, tectonic plate boundaries), which enhances vertical velocities toward the east. The maximum velocities are found to be located in the region where the population density is the highest. They are of the same order as the rates of present‐day global mean sea level rise. Key Points: In the Ganges‐Brahmaputra‐Meghna Delta, the Indian Craton, and the Indo‐Burman subduction zone enhance the subsidence due to sediment loading toward the east The subsidence rate estimates (2–3 mm/year) are comparable to the present‐day global mean sea level rise Subsidence rates are maximum in the most populated area of the delta